THE PHENOMENON OF FORMATION AND FUNCTIONING OF INTEGRATED STRUCTURES IN AGRICULTURAL SECTOR OF RUSSIAN ECONOMY - M. A. Kholodova (Научный журнал Российского НИИ проблем мелиорации, 2021)
Purpose: to study the features of formation and fragility of the functioning of integrated structures of the agrarian sector of the Russian economy. Materials and methods: the methodological research apparatus is based on a comprehensive economic analysis of the financial and economic activities of five backbone integrated formations of the agricultural sector. In order to explain the phenomenon of formation and development of large integrated structures, the data of the annual financial statements of the studied farms were used. Results: the result of the search for alternative forms of inter-farm relations coordination in the agricultural sector of Russian economy was the development of large integrated structures. In the course of the study, their spatial expansion across the territory of Russia was revealed. The economic feasibility of the development of large innovative formations in pig and poultry farming has been substantiated. Particular attention is paid to the mechanism of state support distribution based on market concentration ratios determining the volume of budget allocation for large agribusiness and the Herfindahl-Hirschman index. On the example of the leading backbone agrarian formations, freely adapting to changing economic conditions, the shortcomings of large-format business explaining the phenomenon of their functioning fragility are revealed. In particular, the business capitalization ratio proves the fact of a serious debt load on farms, liquidity ratios demonstrate a low level of their solvency, which in general negatively affects the financial well-being of the largest players in the agricultural market. Conclusions: it is proved that the financial well-being of large integrated formations development is the result of tight belts of farmers, without which it is impossible to obtain credit resources and active government support, which in the mid-run won’t ensure the effective functioning of agricultural production.